Cultural Materialism and Aesthetic Analysis of Ikat-Woven Sarong Production in Parengan Village, Lamongan, East Java - Asmi Nusantari, Okta Viviana; Fitriasari, Rr. Paramita Dyah; Gustami, SP. (Mudra Jurnal Seni Budaya, 2025)
This research investigates the cultural and aesthetic dimensions of ikat-woven sarong production in Parengan Village, Lamongan Regency, East Java, using a material culture biography approach. The research addresses how traditional sarongs—particularly those with legendary patterns such as tempean, botolan, and putihan—function as cultural commodities shaped by communal production, religious practice, and regional identity. Drawing on Raymond Williams’ theory of cultural materialism and Edmund Burke Feldman’s aesthetic theory, the research analyzes the visual structure, motif repetition, and socio-cultural functions of the sarong as both a physical object and a symbolic medium. Data were collected through ethnographic fieldwork, including interviews, visual documentation, and observations in representative weaving centers. The findings reveal that sarong production in Parengan is not only a site of artisanal heritage but also a dynamic cultural practice influenced by commodification, Islamic traditions, and intergenerational knowledge transmission. The research contributes to the discourse on material culture by demonstrating how textile production reflects broader social transformations and cultural negotiations. It highlights the importance of integrating visual analysis and cultural theory to understand the evolving meaning and function of traditional craft in contemporary society.